2018
DOI: 10.3390/molecules24010121
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of C-19 Isosteviol Derivatives as Potent and Highly Selective Antiproliferative Agents

Abstract: Six series of novel isosteviol derivatives; modified in the C-19 position; were synthesized; and their antiproliferative activity was evaluated against three human cancer cell lines (HCT-116; BEL-7402; HepG2) and the human L02 normal cell line in vitro. Most of the derivatives tested here exhibited improved antiproliferative activity with high selectivity when compared with the parent compound isosteviol and the positive control drug 5-fluorouracil. Among these derivatives; compound 5d exhibited the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Derivatives of isosteviol-triazole not only possess anti-colon cancer activity 73 , but also they exhibit anti-multiple cancer cell activity 98 . Compounds with different phenyl 1,2,3-triazole chloroacetamide showed considerably higher antiproliferative activity against the HCT-116 and HepG2 cell lines.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Derivatives of isosteviol-triazole not only possess anti-colon cancer activity 73 , but also they exhibit anti-multiple cancer cell activity 98 . Compounds with different phenyl 1,2,3-triazole chloroacetamide showed considerably higher antiproliferative activity against the HCT-116 and HepG2 cell lines.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The compound UA-1 was synthesised as per the protocol described in a previous study 6 . Ia-Ij (different 1-phenyl-1 H -1,2,3-triazole-4-carbaldehyde) and IIa-IIe (different 2-chloro- N -((1-phenyl-1 H -1,2,3-triazol-4-yl)methyl)acetamide) were prepared as previously described 17 , 20 . IIIa-IIIe were prepared as per Scheme 1: different substitutions of benzoyl hydrazide (10 mmol) and N,N-Dimethylformamide dimethyl acetal (DMFDMA; 1.31 g, 11 mmol) were added to CH 3 CN (20 ml); the resulting mixture was stirred at 60 °C for 1 h. Then, 2-aminoethanol (1.22 g, 20 mmol) and CH 3 COOH (2.40 g, 40 mmol) were added, and the resulting mixture was stirred at 90 °C for 8–12 h. After confirming the reaction progress by TLC, the solvent was evaporated in vacuo .…”
Section: Methodsmentioning
confidence: 99%
“…Tao et al reported that C15 isosteviol-triazole D7 (IC 50 = 2.987 μ M) could exert slightly better inhibitory activity than cisplatin (IC 50 = 3.906 μ M) against HCT-116 cells ( Liu et al, 2016 ). Quan et al reported that C19 isosteviol-triazole D8 could inhibit the growth of several cancer cell lines (HCT-116, BEL-7402, and HepG2) with IC 50 values in the range of 5.38–15.91 μ M, and that was 1.3- to 4.6-fold more potent than the reference drug 5-fluorouracil, and 6.3- to 16.8-fold more potent than the parental isosteviol ( Luan et al, 2019 ). Mechanism studies indicated that D8 could inhibit colony formation and arrest cell cycle (S phase) in HCT-116 cells.…”
Section: Click Chemistry-based Modification Of Terpenoidsmentioning
confidence: 99%